Preservice teachers’ assessment knowledge: Do teaching experiences make a difference? - Lian, Lim Hooi; Yew, Wun Thiam; Meng, Chew Cheng (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2016)
This study aimed to statistically compare preservice teachers’ assessment knowledge in crafting assessment task and selecting assessment method in relation to their teaching experience. This study involved 397 preservice teachers’ who were final year undergraduate students in a local university. The instrument of data collection consisted of eight superitems test. Data collected was analysed by using statistical method (SPSS version 22.0). The result showed that preservice teachers for all categories of teaching experience performed better in the selecting assessment method than crafting assessment task. However, there was no significant differences existed between the three categories of teaching experience of preservice teachers for both standards of assessment knowledge assessed.